2017
DOI: 10.1088/1361-6560/aa77df
|View full text |Cite
|
Sign up to set email alerts
|

Combined passive acoustic mapping and magnetic resonance thermometry for monitoring phase-shift nanoemulsion enhanced focused ultrasound therapy

Abstract: Focused ultrasound (FUS) has the potential to enable precise, image-guided noninvasive surgery for the treatment of cancer in which tumors are identified and destroyed in a single integrated procedure. However, success of the method in highly vascular organs has been limited due to heat losses to perfusion, requiring development of techniques to locally enhance energy absorption and heating. In addition, FUS procedures are conventionally monitored using MRI, which provides excellent anatomical images and can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…When exploiting the thermal effects of vaporized droplets, treatment monitoring may be achieved through magnetic resonance thermometry [85]. Crake et al [86] have shown that changes in proton resonance frequency may be used to measure the temperature change induced by vaporizing DDFP lipid-coated droplets in a polyacrylamide gel phantom.…”
Section: Magnetic Resonance Thermometrymentioning
confidence: 99%
“…When exploiting the thermal effects of vaporized droplets, treatment monitoring may be achieved through magnetic resonance thermometry [85]. Crake et al [86] have shown that changes in proton resonance frequency may be used to measure the temperature change induced by vaporizing DDFP lipid-coated droplets in a polyacrylamide gel phantom.…”
Section: Magnetic Resonance Thermometrymentioning
confidence: 99%
“…The proposed method as an alternative for the current embolization method eliminates the invasive treatment limitations when catheter is utilized [107]. The recent studies illustrated that the NDs emulsion used in the ADV is not only influential due to its noninvasive nature, but also it is possible to harvest the energy absorption and to control the thermal dissipation particularly in highly vascular organs during the cancer treatment [93]. Being able to monitor the heat dissipation helps one to detect the nucleation and cavitation bubbles generation, which is essential in guiding the vaporized droplets to the target properly [108].…”
Section: Recent Developments In the Fieldmentioning
confidence: 99%
“…However, its high cost, lack of portability, long treatment times, and inability to monitor acoustic cavitation-based FUS therapies limits the enthusiasm of MRIgFUS for BBB opening. Ultrasound-guided FUS (USgFUS) systems, stand-alone or in combination with MRI, have the ability to address these limitations (Arvanitis et al, 2013; Wei et al, 2013; Crake et al, 2017).…”
Section: Introductionmentioning
confidence: 99%